750Hospital admissions for patients with rheumatoid arthritis in Western Australia hospitals have declined over time. (2nd September 2021) - Almutairi, Khalid; ,; ,; ,; ,
Abstract: Background: Rheumatoid arthritis (RA) imposes a considerable burden on society in terms of morbidity, long-term disability, and costs. RA prevalence is poorly described in Australia, and linked health datasets can provide a more meaningful picture for RA epidemiology in the Australian population. Methods: We extracted data on all patients identified in the WA Hospital Morbidity Data Collection between 1995 and 2014, with the International Classification of Diseases (ICD) codes for RA (ICD 10 M05.00–M06.99, and the corresponding ICD 9 codes). We estimated period prevalence rates per 1000 hospital separations and annual average percentage changes, with the total number of hospital separations each year. Results: A total of 17, 125 patients were admitted to WA hospitals with a diagnostic code for RA over the study period (1995-2014). The total number of hospital separations for RA patients was 50, 353, indicating an average of three hospital separations per patient over twenty years. The RA prevalence was 3.4 per 1000 separations over the study period, with a -2.89% annual average decrease since 1995. Conclusion: These data demonstrate that hospitalisation for RA has decreased considerably in WA over the last two decades. As this decrease roughly coincides with the introduction of biological drug treatment for RA, the reduced need for hospital admission is likely due to improvements in RA management. Key messages: The RA prevalence was 3.4 per 1000 separations over the study period (1995-2014).